2020
DOI: 10.1002/cpp.2455
|View full text |Cite
|
Sign up to set email alerts
|

Patient personality and psychotherapist reactions in individual psychotherapy setting: a systematic review

Abstract: Despite the importance of psychotherapists' subjective experiencse working with patients with mental issues, little is known about the relationship between therapists' emotional reactions and patients' personality problems. The present study is a systematic review of quantitative research on the association between patients' personality pathology and psychotherapists' emotional, cognitive and behavioural reactions in individual psychotherapy setting. A systematic database search (from January 1980 to August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 78 publications
0
14
1
Order By: Relevance
“…Indeed, it has been found that physicians' emotional responses can negatively influence medical safety [27][28][29]. Effective management of emotional responses occurs only when an individual is capable of tolerating and recognizing these responses and integrating them into a matrix of professional understanding [30,31]. Given that the pandemic may trigger the onset or worsening of psychological distress [12,[32][33][34], there is a considerable need for research that enables a deeper understanding of risk and protective factors for the mental health problems of HCWs during the COVID-19 pandemic, which may help to inform support interventions for HCWs that will, in turn, have a positive impact on their patients.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been found that physicians' emotional responses can negatively influence medical safety [27][28][29]. Effective management of emotional responses occurs only when an individual is capable of tolerating and recognizing these responses and integrating them into a matrix of professional understanding [30,31]. Given that the pandemic may trigger the onset or worsening of psychological distress [12,[32][33][34], there is a considerable need for research that enables a deeper understanding of risk and protective factors for the mental health problems of HCWs during the COVID-19 pandemic, which may help to inform support interventions for HCWs that will, in turn, have a positive impact on their patients.…”
Section: Introductionmentioning
confidence: 99%
“…This can contribute to the level of difficulty in treating clients with more profound or severe personality pathology. Interestingly, Stefana et al (2020) also found that personality pathology was negatively associated with a therapist's feelings of boredom and tiredness. At face value, feeling less bored or tired with a client would be a positive CT experience.…”
Section: Client Factors In Countertransferencementioning
confidence: 97%
“…Stefana et al (2020) 32 conducted a systematic review of quantitative research on the relationship between the personality pathology of the patient and the cognitive, emotional, and behavioural responses of the psychotherapists in individual psychotherapy. Significant relationships between therapist responses and specific personality traits or disorders have been found.…”
Section: Introductionmentioning
confidence: 99%